A new genus and two new species of dactylogyrid monogeneans from gills of Neotropical catfishes (Siluriformes: Doradidae and Loricariidae) - Acosta, Aline Angelina; Scholz, Tomáš; Blasco-Costa, Isabel; Alves, Philippe Vieira; da Silva, Reinaldo José (Parasitology international, 2018)
A new genus of dactylogyrid monogeneans (Ancyrocephalinae), Paracosmetocleithrum n. gen., is erected to accommodate P. trachydorasi n. sp. from Trachydoras paraguayensis (Siluriformes: Doradidae) in the Upper Paraná River basin, Brazil. The new genus differs from Neotropical dactylogyrids in the presence of a well-developed ornamentation in the middle portion of the ventral bar, and a sclerotized patch on the surface of the dorsal bar with an inconspicuous medial process that possesses two submedial projections arising from the tapered ends of this patch. In addition, Demidospermus rhinelepisi n. sp. is described from Rhinelepis aspera (Siluriformes: Loricariidae). The new species, which is the fifth species of the genus described from loricariids, can be differentiated from congeners by the possession of a sclerotized patch attached to the middle portion of the ventral bar, and by morphology of the accessory piece, which presents broad ends, tapering in the centre, rounded proximal end, distal end folding on both sides with folds extending to approximately ¾ of the accessory piece length. Molecular data on both new species are also provided and species composition of Demidospermus, recently revealed as polyphyletic by molecular studies including the present one, is discussed.
Keywords: druhová specificita; Fish Diseases; Brazil; fylogeneze; Integrative taxonomy; Phylogeny; Loricariids; infekce červy třídy Trematoda; RNA helmintů; RNA, Helminth; Species Specificity; South America; Brazílie; Catfishes; RNA ribozomální 28S; Animals; Doradids; zvířata; nemoci ryb; Trematoda; Gills; Trematode Infections; sumci; žábry; RNA, Ribosomal, 28S; Host-associations